Golden and Kuehns, Eds., Western Societies - Primary Sources In Social History - Jirran, Raymond (Teaching History: A Journal of Methods, 1994)
Richard M. Golden and Thomas Kuehn, two professors of Western civilization at Clemson University, offer an anthology of relatively short, complete readings, focused on the "have-nots" of society. In this, the anthology succeeds. The readings are keyed to twenty-one different texts.